2011
DOI: 10.1016/j.ijcard.2009.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Day–night pattern of autonomic nervous system modulation in patients with heart failure with and without sleep apnea

Abstract: Patients with CHF and SA present a reduced and blunted cardiac autonomic modulation across the 24-hour period. These findings may help to explain the increased cardiovascular risk in patients with CHF and SA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
4
10
0
1
Order By: Relevance
“…It has been reported that HRV is an appropriate parameter for estimating autonomic nervous control across a 24-hour period in CHF patients [30], [31], and there is convincing evidence that autonomic nervous imbalance caused by SDB contributes to increased mortality in CHF patients [32]. Our data were concordant with previous reports showing that SDNN and SDANN were also significantly lower in HF patients with SDB [9], [33]. Thus, a blunted HRT and HRV oscillation indicated the impairment of autonomic nervous control and an increased risk for ventricular tachyarrhythmias and sudden cardiac death during the 24-hour period.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that HRV is an appropriate parameter for estimating autonomic nervous control across a 24-hour period in CHF patients [30], [31], and there is convincing evidence that autonomic nervous imbalance caused by SDB contributes to increased mortality in CHF patients [32]. Our data were concordant with previous reports showing that SDNN and SDANN were also significantly lower in HF patients with SDB [9], [33]. Thus, a blunted HRT and HRV oscillation indicated the impairment of autonomic nervous control and an increased risk for ventricular tachyarrhythmias and sudden cardiac death during the 24-hour period.…”
Section: Discussionsupporting
confidence: 92%
“…35 Recently, Ueno et al showed that LF and HF power in CHF patients with SDB were decreased during a 24-h period by increased sympathetic activity and damped circadian oscillation. 36 In the present study, LF and HF powers in patients with SDB were significantly decreased across a 24-h period. The present data are consistent with the findings of Ueno et al 36 SDNN and SDANN were also significantly lower in patients with SDB.…”
Section: Autonomic Nervous System Modulation and Sdbsupporting
confidence: 51%
“…36 In the present study, LF and HF powers in patients with SDB were significantly decreased across a 24-h period. The present data are consistent with the findings of Ueno et al 36 SDNN and SDANN were also significantly lower in patients with SDB. Thus, blunted HRV oscillation indicated impairment of autonomic nervous control and an increase of risk for ventricular tachyarrhythmias and SCD during the 24-h period.…”
Section: Autonomic Nervous System Modulation and Sdbsupporting
confidence: 51%
“…First, although autonomic nervous system unbalance plays an important role in the process of HF [5][6][7][8][9] authors have demonstrated that SCS might exert a cardio-protective effect on HF patients mainly by autonomic modulation [2][3][4]10]. But the pathophysiology of HF is multifactorial and autonomic nervous system chaos may not be the main contributor, thereby autonomic modulation by SCS may not be effective in some patients, such as the patients with acute exacerbation of chronic obstructive pulmonary disease.…”
Section: Dear Editormentioning
confidence: 99%